A new genome allows the identification of genes associated with natural variation in aluminium tolerance in Brachiaria grasses. (16th October 2020) - Worthington, Margaret; Perez, Juan Guillermo; Mussurova, Saule; Silva-Cordoba, Alexander; Castiblanco, Valheria; Cardoso Arango, Juan Andres; Jones, Charlotte; Fernandez-Fuentes, Narcis; Skot, Leif; Dyer, Sarah; Tohme, Joe; Di Palma, Federica; et al.
Abstract: Toxic concentrations of aluminium cations and low phosphorus availability are the main yield-limiting factors in acidic soils, which represent half of the potentially available arable land. Brachiaria grasses, which are commonly sown as forage in the tropics because of their resilience and low demand for nutrients, show greater tolerance to high concentrations of aluminium cations (Al 3+ ) than most other grass crops. In this work, we explored the natural variation in tolerance to Al 3+ between high and low tolerant Brachiaria species and characterized their transcriptional differences during stress. We identified three QTLs (quantitative trait loci) associated with root vigour during Al 3+ stress in their hybrid progeny. By integrating these results with a new Brachiaria reference genome, we identified 30 genes putatively responsible for Al 3+ tolerance in Brachiaria . We observed differential expression during stress of genes involved in RNA translation, response signalling, cell wall composition, and vesicle location homologous to aluminium-induced proteins involved in limiting uptake or localizing the toxin. However, there was limited regulation of malate transporters in Brachiaria, which suggests that exudation of organic acids and other external tolerance mechanisms, common in other grasses, might not be relevant in Brachiaria . The contrasting regulation of RNA translation and response signalling suggests that response timing is critical in high Al 3+ -tolerant Brachiaria . Abstract : We identified QTLs, genes, and molecular responses in high and low tolerant Brachiaria grasses associated with aspects of the response to aluminium stress, such as regulation, cell wall composition, and active transport.